2016
DOI: 10.1080/17461391.2016.1251496
|View full text |Cite
|
Sign up to set email alerts
|

A prospective examination of the impact of high levels of exercise training on sedentary behaviour

Abstract: The aim of this study is to determine changes in sedentary behaviour in response to extensive aerobic exercise training. Participants included adults who self-selected to run a marathon. Sedentary behaviour, total activity counts and physical activity (PA) intensity were assessed (Actigraph GT3X) for seven consecutive days during seven assessment periods (−3, −2, and —1 month prior to the marathon, within 2 weeks of the marathon, and +1, +2, and +3 months after the marathon). Models were fitted with multiple i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
9
2
Order By: Relevance
“…Despite documented increases in VPA and mean accelerometer measured activity (cpm), they observed no significant difference in mean SB. However, the participants in the study by Swartz et al (2016) were healthy adult marathon runners with substantially lower BMI and age compared to the participants in the present study, which may contribute to the discrepancy with our results.…”
Section: Discussioncontrasting
confidence: 81%
“…Despite documented increases in VPA and mean accelerometer measured activity (cpm), they observed no significant difference in mean SB. However, the participants in the study by Swartz et al (2016) were healthy adult marathon runners with substantially lower BMI and age compared to the participants in the present study, which may contribute to the discrepancy with our results.…”
Section: Discussioncontrasting
confidence: 81%
“…The Sedentary group showed the highest mean sedentary PA per hour of waking time, while the Balanced group presented the highest mean MVPA per hour of waking time, and the Hazardous group had the lowest sedentary PA and MVPA. Both Sedentary and Balanced, however, achieve the WHO daily recommended levels of MVPA, considering the mean wear time for the sample of this study was 11 h. Previous studies have reported that PA and SED are distinct domains not only for those who do not meet the recommended guideline levels, but also for those who do, including young people [39] and athletes [10,40].…”
Section: Discussionmentioning
confidence: 87%
“…All studies were written in English and performed in eight different countries predominantly originating from Portugal (n=3). The studies included athletes from various disciplines including cross-country skiers (Alméras et al, 1991), university students with 9 different sports [cycling, hockey, kayaking, rugby, netball, athletics, water sports and rowing] (Clemente, Nikolaidis, Martins, & Mendes, 2016;Driller, Dixon, & Clark, 2017), triathlon (Drenowatz, Eisenmann, Pivarnik, Pfeiffer, & Carlson, 2013), cycling (Drenowatz et al, 2013;Pollock et al, 2018), running (Drenowatz et al, 2013;Exel, Mateus, Abrantes, Leite, & Sampaio, 2019;Rantalainen, Pesola, Quittner, Ridgers, & Belavy, 2018;Swartz, Miller, Cho, Welch, & Strath, 2017;Whitfield, Pettee Gabriel, & Kohl, 2014), football (Exel et al, 2019;Weiler, Aggio, Hamer, Taylor, & Kumar, 2015), elite athletes from different disciplines [long-distance running, road cycling, triathlon, judo, taekwondo, swimming, sailing, tennis, handball, track and field athletics and pentathlon] (Júdice, Silva, Magalhães, Matias, & Sardinha, 2014) and rowing . McCracken et al only reported different sport categories which consisted of snow/ice, water, team, skill, racquet, multi, endurance, lifting, urban and others (McCracken & Dogra, 2018).…”
Section: Resultsmentioning
confidence: 99%